Microevolution of Outbreak-Associated Middle East Respiratory Syndrome Coronavirus, South Korea, 2015 - Seong, Moon-Woo (Emerg Infect Dis, 2016)
During the 2015 Middle East respiratory syndrome coronavirus outbreak in South Korea, we sequenced full viral genomes of strains isolated from 4 patients early and late during infection. Patients represented at least 4 generations of transmission. We found no evidence of changes in the evolutionary rate and no reason to suspect adaptive changes in viral proteins.